Competitive Advantage, Strategic Human Resource Practice, Knowledge Management and Corporate Social Responsibility - Ni Luh Putu Eka Yudi Prastiwi; A.A.N. Oka Suryadinatha Gorda (Jurnal Manajemen dan Bisnis, 2016)
The purpose of this study was to determine how to improve the Sustainable CompetitiveAdvantage in the face of all the changes. This study uses a quantitative approach. Datacollection techniques used in this study was a questionnaire / questionnaire measuringdevices in the form of Agree-Disagree Scale, which were selected for the study is the LPDboard in Buleleng many as 53 people. Data analysis techniques used in this study is astructural equation model (Structural Equation Modeling-SEM) based variance orComponent based SEM, the famous so-called Partial Least Square (PLS) Visual version 2.0.All relationships are examined in this study showed a positive and significant. This studyrecommends, in order to improve the Sustainable Competitive Advantage, the LPD canimplement the Strategic Human Resource Practice, Knowledge Management and CorporateSocial ResponsibilityKeywords : Sustainable Competitive Advantage, Strategic Human Resource Practice,Knowledge Management and Corporate Social Responsibility.